Problems of Hasad from the Perspective of the Qur'an (Review of Maqashidi Interpretation) - Muhammad Chasan; Nyoko Adi Kuswoyo; Wiwin Ainis Rohti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Envy (Hasad) is a psychological illness with significant psychological, moral, and social impacts. It is a spiritual disease that can lead to various forms of evil, such as slander, ridicule, humiliation, and persecution. This study examines the problematics of hasad from the perspective of the Qur'an using the Tafsir Maqashidi approach, a method of interpretation that emphasizes the objectives and wisdom (maqashid) behind Islamic teachings. The Qur'an highlights the roots, manifestations, and impacts of hasad, while also providing spiritual guidance for overcoming and preventing it. The central issues addressed in this research are: What forms of problematics arise from hasad in life according to the Qur'anic perspective? How does the concept of Maqashid Asy-Syari'ah in Qur'anic verses about hasad relate to the issues caused by it? The objectives of this research are to identify and analyze the various forms of problematics caused by hasad in daily life based on the Qur'anic perspective. Furthermore, the study aims to explain the concept of Maqashid Asy-Syari'ah in Qur'anic verses related to hasad and how this concept provides solutions to the issues arising from it. Additionally, the research seeks to reveal the relevance of the Qur'anic teachings in addressing the negative impacts of hasad, both at the individual and social levels.